2018
DOI: 10.1097/brs.0000000000002221
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Explanted Magnetically Controlled Growing Rods From Seven UK Spinal Centers

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 30 publications
2
56
1
1
Order By: Relevance
“…Moreover, titanium wear from joint replacements has been shown to induce aneuploidy in vitro and in vivo. The potential links of titanium wear debris to metallosis in children fitted with spinal implants have recently been described …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, titanium wear from joint replacements has been shown to induce aneuploidy in vitro and in vivo. The potential links of titanium wear debris to metallosis in children fitted with spinal implants have recently been described …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the magnetically actuated rods only generate 42 pounds of axial force and may fail to generate enough force to elongate after several lengthening procedures. There are also issues related to titanium wear debris noted at the time of device removal [52]. Generally, these devices have made important improvements in the treatment of severe curves seen in young children with PWS.…”
Section: Non-fusion Spinal Instrumentation With Expandable Implantsmentioning
confidence: 99%
“…26 Analysis of explanted magnetic expansion control growing rods showed that with the achieved growth during distraction, high volumes of Ti wear debris were formed. 27 These findings emphasize the challenge to address metallosis in EOS surgery.…”
Section: Discussionmentioning
confidence: 93%